Risk Factors Of Stroke: Literature Review - Oliveira, Adirson Barbosa de; Muhith, Abdul; Zahro, Chilyatiz (Chakra Brahmanda Lentera Institute, 2023)
Background: Stroke is the most common cause of disease in the world and is the highest cause of death in Indonesia, so prevention is very important to minimise the incidence of stroke. The most appropriate effort to prevent stroke is to control stroke risk factors. The purpose of the literature review is to analyse the risk factors associated with stroke events in patients. Methods: The method used is a literature review using a journal database from Pubmed, Science Direct, and Google Scholar. In the 2019-2023 range, with the keywords